Quantitative aortography for assessment of aortic regurgitation in the era of percutaneous aortic valve replacement - Abdelshafy, Mahmoud; Serruys, Patrick W.; Tsai, Tsung-Ying; Revaiah, Pruthvi Chenniganahosahalli; Garg, Scot; Aben, Jean-Paul; Schultz, Carl J.; Abdelghani, Mohammad; Tonino, Pim A. L.; Miyazaki, Yosuke; Rutten, Marcel C. M.; Cox, Martijn; et al. (Frontiers in Cardiovascular Medicine, 2023)
Paravalvular leak (PVL) is a shortcoming that can erode the clinical benefits of transcatheter valve replacement (TAVR) and therefore a readily applicable method (aortography) to quantitate PVL objectively and accurately in the interventional suite is appealing to all operators. The ratio between the areas of the time-density curves in the aorta and left ventricular outflow tract (LVOT-AR) defines the regurgitation fraction (RF). This technique has been validated in a mock circulation; a single injection in diastole was further tested in porcine and ovine models. In the clinical setting, LVOT-AR was compared with trans-thoracic and trans-oesophageal echocardiography and cardiac magnetic resonance imaging. LVOT-AR>17% discriminates mild from moderate aortic regurgitation on echocardiography and confers a poor prognosis in multiple registries, and justifies balloon post-dilatation. The LVOT-AR differentiates the individual performances of many old and novel devices and is being used in ongoing randomized trials and registries.